Method for controlling structure content in dual-phase steel and dual-phase steel

By adjusting the Mn content and laminar flow cooling process parameters, the problem of controlling the martensite structure content in duplex steel is solved, and the high-performance preparation of duplex steel is achieved at low alloy cost, improving its mechanical properties and forming properties.

CN119220909APending Publication Date: 2024-12-31PANZHIHUA IRON & STEEL RES INST OF PANGANG GROUP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411350830.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The prior art has not yet provided an effective method to control the martensite structure content in hot-rolled duplex steels, affecting their forming performance and use performance.

Method used

By adjusting the Mn content and laminar flow cooling process parameters, especially the air cooling time, the ferrite and martensite content in duplex steel are accurately controlled, the heating temperature and rolling deformation amount are optimized, and the mechanical properties and service performance of the steel plate are ensured.

Benefits of technology

The precise control of ferrite and martensite content in duplex steel at low alloy cost is achieved, which improves the yield strength, tensile strength and elongation of the steel plate, reduces production costs, and improves the forming performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119220909A_ABST
    Figure CN119220909A_ABST
Patent Text Reader

Abstract

The invention discloses a control method for the structure content in dual-phase steel and the dual-phase steel, and belongs to the technical field of steelmaking. In order to achieve accurate control over the content of ferrite and martensite in the dual-phase steel, the control method for the structure content in the dual-phase steel is provided, and the dual-phase steel comprises 0.05%-0.07% of C, 0.55%-1.15% of Mn, 0.10%-0.30% of Si, smaller than or equal to 0.020% of P, smaller than or equal to 0.010% of S, 0.030%-0.050% of Als, 0.50%-0.70% of Cr, 0.010%-0.030% of Nb and the balance Fe and inevitable impurities. The low-cost Mn-Cr-Nb microalloying thought is adopted, the heating temperature, the in-furnace time and the rolling and laminar cooling process are optimized, the Mn content and the air cooling time are adjusted, accurate control over the content of ferrite and martensite is achieved, the performance of the dual-phase steel is guaranteed, and the production cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of steelmaking, and in particular relates to a method for controlling the structure content in a dual-phase steel and the dual-phase steel. Background Art

[0002] In recent years, the automobile manufacturing industry has developed rapidly, and higher requirements have been put forward for the lightweight and safety of automobile steel. Dual-phase steel (DP steel) is widely used in the manufacture of wheel spokes and rims, beams, brackets, anti-collision reinforcement components and other parts due to its low yield strength ratio, good forming, hole expansion and work hardening properties. The microstructure of dual-phase steel is composed of ferrite and martensite, in which martensite is dispersed in the continuous ferrite phase in an island shape. The ferrite and martensite phases play the role of improving toughness and strength respectively, but the martensite content has a huge impact on the forming properties of the material. How to achieve stable control of martensite content in industry plays a vital role in the promotion and application of hot-rolled dual-phase steel.

[0003] CN115029622B discloses a high surface quality hot-rolled dual-phase steel and its production process, wherein the steel has the following components: 0.05-0.068% C, Si≤0.09%, 1.2-1.5% Mn, 0.02-0.06% Als, 0.5-0.7% Cr, P≤0.015-0.025%, S≤0.002%, N≤0.006%, and the balance is Fe. The preparation process is provided as follows: the furnace temperature is 1280-1320°C, the heating time is 150-220min, the finishing rolling temperature is 790-830°C, the rolling speed is 3.1-6m / s, the cooling rate is 100-140°C / s, the temperature drop is 100-130°C, followed by air cooling for 7-12s, and then cooling to below 250°C at a cooling rate of 85-115°C / s.

[0004] CN114480951B discloses a hot-rolled dual-phase steel plate with a tensile strength of 700 MPa and a manufacturing method thereof, wherein the chemical composition of the steel is: C: 0.08-0.12%, Si: 0.10-0.15%, Mn: 1.30-1.50%, P≤0.015%, S≤0.003%, Cr: 0.50-0.70%, Ti: 0.015-0.025%, Mg: 0.0007-0.0020%, Alt: 0.020-0.050%, and the remainder is Fe and unavoidable impurities; Production process The method is as follows: the end temperature of rough rolling is 990-1020°C; the end temperature of finishing rolling is 810-850°C; the reduction rate of finishing rolling is 85-92%; after finishing rolling, laminar cooling adopts a three-stage cooling method, the first stage is water cooling, the cooling rate is 60-100°C / s, and the end temperature of the first stage cooling is 700-720°C; the second stage is air cooling, the air cooling time is 5-7s, and the cooling rate is 10-15°C / s; the third stage is water cooling, the cooling rate is 60-200°C / s, the end temperature of the third stage cooling is ≤200°C, and the coiling temperature is 50-150°C to obtain the hot rolled steel coil.

[0005] CN111363901B discloses a high surface quality ferrite martensite hot rolled dual phase steel and a manufacturing method thereof, wherein the weight percentage of the components is: C: 0.04-0.08%, Si: ≤0.1%, Mn: 1.0-1.4%, Al: 0.3-0.8%, Cr: 0.15-0.60%, Nb: 0.01-0.03%, P≤0.015%, S≤0.002%, N: ≤0.005%, and also includes adding one or more of the following elements, T i≤0.03%, V≤0.03%, Ca≤0.005%, and the rest are Fe and inevitable impurities. The preparation process is: heating the steel billet with the above composition at 1150-1250°C, rolling it in the austenite region, with a rolling deformation of 80-95%, a final rolling temperature of 820-880°C, cooling the steel plate after final rolling to 630-730°C at a cooling rate of 50-150°C / s, air cooling for 3-15 seconds, and then cooling it again to below 300°C at a cooling rate of more than 60°C / s and coiling it.

[0006] As can be seen from the above, the existing process of hot-rolled dual-phase steel mainly involves the composition and process control requirements of dual-phase steels of different strength levels, and there are no reports on the method of controlling the microstructure content in dual-phase steel. Summary of the invention

[0007] The purpose of the present invention is to achieve accurate control of the ferrite and martensite contents in dual-phase steel while using low alloy cost, and to ensure that the dual-phase steel has excellent mechanical properties and performance.

[0008] To achieve the above object, the present invention first provides a method for controlling the microstructure content in a dual-phase steel, wherein the dual-phase steel comprises the following chemical components by weight percentage: C: 0.05% to 0.07%, Mn: 0.55% to 1.15%, Si: 0.10% to 0.30%, P≤0.020%, S≤0.010%, Als: 0.030% to 0.050%, Cr: 0.50% to 0.70%, Nb: 0.010% to 0.030%, and the rest is Fe and unavoidable impurities;

[0009] The production process of the dual-phase steel is (electric furnace or converter) smelting - refining - continuous casting - slab heating - rough rolling - finishing rolling - laminar cooling - coiling process; wherein, the laminar cooling adopts water cooling + air cooling + water cooling, the starting cooling temperature is 800°C ~ 850°C, the first stage water cooling cooling rate is 10°C / s ~ 30°C / s, after cooling to 680°C ~ 700°C, air cooling, air cooling time is 6s ~ 12s, the second stage water cooling cooling rate is 20°C / s ~ 50°C / s, cooling to 100°C ~ 200°C.

[0010] On the basis of the above, the present invention achieves more precise control of the ferrite and martensite contents in the dual-phase steel by adjusting the Mn content and the laminar cooling and air cooling time.

[0011] Wherein, in the control method of the microstructure content in the dual-phase steel, the dual-phase steel includes the following chemical components by weight percentage: C: 0.05% to 0.07%, 0.55%≤Mn<0.75%, Si: 0.10% to 0.30%, P≤0.020%, S≤0.010%, Als: 0.030% to 0.050%, Cr: 0.50% to 0.70%, Nb: 0.010% to 0.030%, and the rest is Fe and unavoidable impurities;

[0012] The production process of the dual-phase steel is (electric furnace or converter) smelting - refining - continuous casting - slab heating - rough rolling - finishing rolling - laminar cooling - coiling process; wherein, the laminar cooling adopts water cooling + air cooling + water cooling, the start cooling temperature is 800°C ~ 850°C, the first stage water cooling cooling rate is 10°C / s ~ 30°C / s, after cooling to 680°C ~ 700°C, air cooling, 6s≤air cooling time <8s, the second stage water cooling cooling rate is 20°C / s ~ 50°C / s, cooling to 100°C ~ 200°C.

[0013] Wherein, in the control method of the microstructure content in the dual-phase steel, the dual-phase steel includes the following chemical components by weight percentage: C: 0.05% to 0.07%, 0.75%≤Mn<0.95%, Si: 0.10% to 0.30%, P≤0.020%, S≤0.010%, Als: 0.030% to 0.050%, Cr: 0.50% to 0.70%, Nb: 0.010% to 0.030%, and the rest is Fe and unavoidable impurities;

[0014] The production process of the dual-phase steel is (electric furnace or converter) smelting - refining - continuous casting - slab heating - rough rolling - finishing rolling - laminar cooling - coiling process; wherein, the laminar cooling adopts water cooling + air cooling + water cooling, the start cooling temperature is 800°C ~ 850°C, the first stage water cooling cooling rate is 10°C / s ~ 30°C / s, after cooling to 680°C ~ 700°C, air cooling, 8s≤air cooling time <10s, the second stage water cooling cooling rate is 20°C / s ~ 50°C / s, cooling to 100°C ~ 200°C.

[0015] Wherein, in the control method of the microstructure content in the above-mentioned dual-phase steel, the dual-phase steel includes the following chemical components by weight percentage: C: 0.05% to 0.07%, 0.95%≤Mn≤1.15%, Si: 0.10% to 0.30%, P≤0.020%, S≤0.010%, Als: 0.030% to 0.050%, Cr: 0.50% to 0.70%, Nb: 0.010% to 0.030%, and the rest is Fe and unavoidable impurities;

[0016] The production process of the dual-phase steel is (electric furnace or converter) smelting - refining - continuous casting - slab heating - rough rolling - finishing rolling - laminar cooling - coiling process; wherein, the laminar cooling adopts water cooling + air cooling + water cooling, the start cooling temperature is 800°C ~ 850°C, the first stage water cooling cooling rate is 10°C / s ~ 30°C / s, after cooling to 680°C ~ 700°C, air cooling, 10s≤air cooling time≤12s, the second stage water cooling cooling rate is 20°C / s ~ 50°C / s, cooling to 100°C ~ 200°C.

[0017] Among them, the method for controlling the microstructure content in the above-mentioned dual-phase steel is that in the slab heating process, the slab heating temperature is 1190°C~1230°C, the slab is in the furnace for a time of ≥100min when hot-charged, and the slab is in the furnace for a time of ≥150min when cold-charged.

[0018] Among them, the method for controlling the microstructure content in the above dual-phase steel is to use 5 to 6 rolling passes in the rough rolling process, and the reduction amount of a single pass is ≥18%.

[0019] Among them, in the above-mentioned method for controlling the microstructure content in the dual-phase steel, in the finishing rolling process, the finishing rolling adopts 6 to 7 rolling passes, and the cumulative compression ratio is 6 to 12.

[0020] Among them, in the above-mentioned method for controlling the microstructure content in the dual-phase steel, in the finishing rolling process, the finishing rolling adopts constant speed rolling, and the finishing rolling exit speed is 5.5m / s to 6.0m / s.

[0021] Among them, in the above-mentioned method for controlling the microstructure content in the dual-phase steel, in the finishing rolling process, the thickness of the steel plate obtained after finishing rolling is 3.0mm to 6.0mm.

[0022] The present invention also provides a dual-phase steel, which is prepared by adopting the above method.

[0023] The microstructure of the dual-phase steel is ferrite+martensite, wherein the volume fraction of ferrite is 85% to 90%, the volume fraction of martensite is 10% to 15%, and the average grain size is 5 μm to 15 μm.

[0024] The yield strength of the dual-phase steel is 330MPa-470MPa, the tensile strength is 580MPa-700MPa, the elongation is ≥24%, the yield strength ratio is ≤0.80, and the 180° cold bending test d=0 is qualified.

[0025] In the present invention, the operations or parameters in the steps not specially marked, such as smelting, refining, continuous casting, coiling and the like, all adopt the conventional methods in the art.

[0026] Beneficial effects of the present invention:

[0027] The present invention adopts the Mn-Cr-Nb microalloying concept with low alloy cost, and accurately controls the heating temperature and the furnace time according to the specific composition characteristics of the dual-phase steel; performs rough rolling in the austenite recrystallization temperature range, performs fine rolling in the austenite non-recrystallization temperature range, and strictly controls the deformation amount and compression ratio, so as to provide sufficient nucleation points for the subsequent ferrite phase transformation and promote the ferrite grain refinement; optimizes key laminar cooling process parameters, such as cooling rate, air cooling temperature, air cooling time, coiling temperature, etc., to achieve precise control; in particular, by adjusting the Mn content and the laminar cooling air cooling time, the ferrite and martensite contents that have a great influence on the mechanical properties and performance of the dual-phase steel are accurately controlled, thereby ensuring the performance of the dual-phase steel and reducing the production cost.

[0028] The method for controlling the content of multiphase structure in the present invention can be implemented on conventional hot rolling and continuous casting and rolling production lines, and the method can be extended to the preparation of multiphase structure steels such as hot-rolled iron steel and hot-rolled complex phase steel. The method is highly operable and widely applicable. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 Phase diagram of dual-phase steel with different Mn contents.

[0030] Figure 2 This is the microstructure diagram of the steel in Example 1.

[0031] Figure 3 This is the microstructure diagram of the steel in Example 2.

[0032] Figure 4 This is the microstructure diagram of the steel in Example 3.

[0033] Figure 5 This is the microstructure diagram of the steel in comparative example 1.

[0034] Figure 6 This is the microstructure diagram of the steel in comparative example 2.

[0035] Figure 7 This is the microstructure diagram of the steel in comparative example 3. DETAILED DESCRIPTION

[0036] The present invention provides a method for controlling the microstructure content in a dual-phase steel. The reasons for limiting the main alloying elements in the steel of the present invention are described below.

[0037] C is an important interstitial solid solution strengthening element and martensite forming element in steel. When the carbon content is too low, the carbon content in martensite is too low, which will lead to a decrease in material strength. At the same time, the steel of the present invention uses ferrite as the main organizational type. Reducing the carbon content is conducive to increasing the ferrite ratio and improving the forming performance of the material. The present invention limits the C content to a relatively low level of 0.05-0.07%.

[0038] Si can increase the activity of C during the phase transformation process and promote the diffusion of C from ferrite to austenite during the phase transformation process. On the one hand, it plays a role in purifying ferrite, and on the other hand, it makes austenite carbon-rich during the phase transformation process, which is beneficial to the subsequent martensitic phase transformation. However, when the Si content is too high, red iron oxide scale is easily formed on the surface of the steel plate. Therefore, the present invention reduces the Si content to a lower level, 0.10% to 0.30%.

[0039] Mn is an austenite stabilizing element. Increasing the Mn content is beneficial to improving the stability of austenite during the phase transformation process, promoting the retention of austenite in the laminar cooling air cooling stage, and transforming into martensite in the subsequent second water cooling process. Thermodynamic research results show that (see Figure 1 ), as the Mn content increases, the austenite content is higher and the ferrite content is lower at the same temperature, and the martensite content transformed from austenite during the phase transformation process is higher. Therefore, the present invention controls the Mn content in the range of 0.55-1.15%, and proposes different laminar cooling processes for different Mn content control intervals (0.55%≤Mn<0.75%, 0.75%≤Mn<0.95% and 0.95%≤Mn≤1.15%).

[0040] P and S are impurity elements in steel, which are easy to form inclusions and reduce the toughness and plasticity of the steel. Therefore, the present invention limits the P content to ≤0.020% and the S content to ≤0.010%.

[0041] Als plays a major role in deoxidation in steel, and therefore, the Als content is controlled within a range of 0.030-0.050% in the present invention.

[0042] Cr can improve the hardenability of steel, increase the cooling rate of the core of the steel plate, and enable the steel plate to undergo low-temperature martensitic transformation throughout the thickness direction, thereby obtaining a ferrite-martensite dual-phase structure. The present invention requires the addition of 0.50% to 0.70% Cr.

[0043] Nb forms NbC precipitation phase during the finishing rolling process. The formed precipitation phase and the solid-solution Nb can pin the austenite grain boundary during the rolling process, refine the austenite grains, and promote the refinement of the final ferrite structure. In addition, Nb can inhibit pearlite transformation. Therefore, 0.010% to 0.030% of Nb is added in the present invention.

[0044] The reasons for limiting the main production process parameters of the steel described in the present invention are explained below.

[0045] First, in terms of the heating system. Since a large amount of microalloying elements are not added to the steel described in the present invention, the main microalloying elements are Cr and Nb, and the solid solution temperature of the above elements is relatively low, so the required value of the slab heating temperature is not high, which is 1190℃~1230℃. At the same time, there is no requirement for hot delivery and hot loading when the slab is heated. During hot delivery and hot loading, since the temperature of the slab is high when it enters the furnace, the time in the furnace can be appropriately reduced. During cold loading, since the temperature of the slab is reduced when it enters the furnace, the time in the furnace can be appropriately extended to promote uniform heating and temperature uniformity inside and outside the slab. Therefore, the present invention requires that the time in the furnace for the slab when hot loading is ≥100min, and the time in the furnace for the slab when cold loading is ≥150min.

[0046] Second, in terms of rolling process. Rough rolling requires rolling in the austenite recrystallization temperature range. Therefore, the present invention requires that the deformation of a single rough rolling pass is ≥ 18% to ensure that austenite recrystallization occurs during each rough rolling deformation to promote grain refinement. If the deformation of a single rough rolling pass is low, it is easy to cause insufficient deformation of the core of the slab, incomplete recrystallization, and coarse structure in the core of the finished steel plate. Finishing rolling requires rolling in the temperature range of the austenite non-recrystallization zone. Therefore, the present invention requires the cumulative deformation of finishing rolling, that is, the cumulative compression ratio is required to be 6 to 12, to ensure the flattening of austenite, provide sufficient nucleation points for the subsequent ferrite phase transformation, and promote ferrite grain refinement.

[0047] Third, in terms of laminar cooling process. Phase change occurs during laminar cooling, which is the most critical process to determine the microstructure type and microstructure content of dual-phase steel. The details are as follows:

[0048] (1) The present invention requires that the finishing rolling adopts constant speed rolling, and the finishing rolling exit speed is 5.5 m / s to 6.0 m / s. This is because the constant speed rolling is conducive to the solidification of the laminar cooling model, that is, the water header in each stage of the laminar cooling "water cooling + air cooling + water cooling" model is fixed, thereby stabilizing the microstructure content of the dual-phase steel.

[0049] (2) The present invention requires that the laminar cooling start temperature be 800°C to 850°C. When the start temperature is too high, the size of the original austenite increases, the stability of the austenite increases, and the martensite content increases. On the contrary, when the cracking temperature is too low, the final stand of the finishing rolling mill may enter the two-phase zone for rolling, which may easily form a banded ferrite structure on the surface of the steel plate, affecting the toughness of the material.

[0050] (3) The present invention requires that the cooling rate of the first stage of water cooling be 10°C / s to 30°C / s in order to allow the steel plate to undergo a rapid ferrite phase transformation. If the cooling rate is too low, it is easy to cause the phase transformation to enter the pearlite transformation range.

[0051] (4) The present invention requires an air cooling temperature of 680°C to 700°C. If the air cooling temperature is too low, the steel may enter the pearlite transformation zone during a water cooling step, forming an abnormal pearlite structure. If the air cooling temperature is too high, the diffusion rate of carbon and iron atoms will be promoted. The ferrite phase transformation is a diffusion-type phase transformation. At a higher air cooling temperature, it is easy to obtain an excessively high ferrite ratio, resulting in a decrease in the martensite content, which in turn leads to a low tensile strength of the steel.

[0052] (5) The present invention requires an air cooling time of 6s to 12s. Similarly, since the ferrite phase transformation is a diffusion-type phase transformation, if the air cooling time is too low, it is easy to cause the ferrite content to decrease and the martensite content to increase; if the air cooling time is too high, it is easy to cause the ferrite content to increase and the martensite content to decrease. Therefore, in order to achieve stable control of the martensite content, the present invention limits the air cooling time to the range of 6s to 12s.

[0053] (6) The second stage of water cooling requires that the residual metastable austenite structure in the air cooling stage be transformed into a martensite structure. Therefore, the second stage of water cooling rate is set at a relatively high level, which is required to be no less than 20°C / s. At the same time, when the cooling rate is too high, the phase transformation supercooling degree will increase, causing the martensite structure morphology to change from a dispersed distribution to a chain-like segregated distribution. Therefore, the present invention limits the second stage of water cooling cooling rate to 20°C / s to 50°C / s.

[0054] (7) The second stage of water cooling requires a martensitic phase transformation, so the final cooling temperature is required to be lower than the martensitic transformation temperature. However, the final cooling temperature should not be too low, otherwise the martensitic structure will be distributed in a chain-like manner due to the increase in supercooling of the phase transformation. The present invention limits the final cooling temperature to 100°C to 200°C.

[0055] In addition, the present invention proposes different laminar cooling air cooling time requirements for dual-phase steels with different Mn contents, which is conducive to realizing personalized needs. When the Mn content is low, 0.55%≤Mn<0.75%, since the reduction of Mn content will lead to a reduction in martensite content, the air cooling time should be appropriately reduced to increase the martensite content. At this time, the present invention limits the air cooling time to 6s≤air cooling time<8s. Correspondingly, when the Mn content is 0.75%≤Mn<0.95%, the air cooling time is limited to 8s≤air cooling time<10s, and when the Mn content is 0.95%≤Mn≤1.15%, the air cooling time is limited to 10s≤air cooling time≤12s.

[0056] The present invention controls the composition of dual-phase steel and optimizes the process in a targeted manner, thereby achieving stable trial production of hot-rolled dual-phase steel at a relatively low alloy cost, promoting the improvement of the controlled rolling and controlled cooling process level of hot-rolled high-strength steel, and broadening the product series of automotive steel. The profit generated by a ton of steel is RMB 500, and the annual output is RMB 3,000 tons, creating a profit of RMB 1.5 million per year.

[0057] The present invention is further described in detail below by way of examples, but the protection scope of the present invention is not limited to the scope of the examples.

[0058] Example 1

[0059] A steel billet with a thickness of 200 mm and the following chemical compositions by weight percentage was prepared by a converter-LF electric heating-RH vacuum refining-continuous casting process: 0.06% C, 0.66% Mn, 0.15% Si, 0.010% P, 0.005% S, 0.038% Als, 0.55% Cr, 0.023% Nb, and the remainder being Fe and unavoidable impurities.

[0060] The steel billet is heated-rough rolling-hot coil box-finishing rolling-laminar cooling process to prepare a 4.0mm thick steel plate. The specific process is as follows: the slab is cold loaded into the furnace, the heating temperature is 1213℃, and the furnace time is 165min. The rough rolling adopts 5 passes, and the deformation of each pass is 21%, 22%, 26%, 32%, and 32% respectively. The thickness of the intermediate billet after rough rolling is 42mm. The finishing rolling adopts 7 passes, the cumulative compression ratio is 10.5, the finishing rolling adopts constant speed rolling, and the finishing rolling exit speed is 5.8m / s. The laminar cooling opening temperature is 810℃, the first stage water cooling cooling rate is 15.9℃ / s, the air cooling temperature is 695℃, the air cooling time is 7.5s, the second stage water cooling cooling rate is 36.7℃ / s, and the coiling temperature is 195℃.

[0061] The steel microstructure of Example 1 is 86.2% ferrite and 13.8% martensite, with an average grain size of 8.0 μm. The microstructure morphology is shown in the attached Figure 2, yield strength 421MPa, tensile strength 609MPa, yield strength ratio 0.69, elongation 27.0%, 180° cold bending d=0 without cracking.

[0062] Example 2

[0063] The process flow of converter-LF electric heating-RH vacuum refining-continuous casting was adopted to prepare a steel billet with a thickness of 230 mm and the following chemical compositions by weight percentage: 0.07% C, 0.89% Mn, 0.24% Si, 0.013% P, 0.006% S, 0.041% Als, 0.64% Cr, 0.018% Nb, and the rest Fe and unavoidable impurities.

[0064] The steel billet is heated-rough rolling-hot coil box-finishing rolling-laminar cooling process to prepare a 4.5mm thick steel plate. The specific process is as follows: the slab is hot loaded into the furnace, the heating temperature is 1195℃, and the furnace time is 144min. The rough rolling adopts 6 rolling passes, and the deformation of each pass is 19%, 21%, 23%, 27%, 31%, and 32% respectively. The thickness of the intermediate billet after rough rolling is 40mm. The finishing rolling adopts 6 rolling passes, the cumulative compression ratio is 8.8, the finishing rolling adopts constant speed rolling, and the finishing rolling exit speed is 5.9m / s. The laminar cooling opening temperature is 829℃, the first stage water cooling cooling rate is 16.6℃ / s, the air cooling temperature is 687℃, the air cooling time is 9.0s, the second stage water cooling cooling rate is 45.7℃ / s, and the coiling temperature is 135℃.

[0065] The steel microstructure of Example 2 is 86.5% ferrite and 13.5% martensite, with an average grain size of 7.5 μm. The microstructure morphology is shown in the attached Figure 3 , yield strength 443MPa, tensile strength 618MPa, yield strength ratio 0.72, elongation 28.5%, 180° cold bending d=0 without cracking.

[0066] Example 3

[0067] The process flow of converter-LF electric heating-RH vacuum refining-continuous casting was adopted to prepare a steel billet with a thickness of 230 mm and the following chemical compositions by weight percentage: 0.05% C, 1.09% Mn, 0.25% Si, 0.013% P, 0.004% S, 0.038% Als, 0.52% Cr, 0.028% Nb, and the rest being Fe and unavoidable impurities.

[0068] The steel billet is heated-rough rolling-hot coil box-finishing rolling-laminar cooling-slow cooling process to prepare a 5.0mm thick steel plate. The specific process is as follows: the steel billet is sent into the slab heating furnace by hot delivery and hot charging, the furnace temperature is 1223℃, and the furnace time is 130min. The rough rolling adopts 6 passes, and the deformation of each pass is 18%, 21%, 24%, 27%, 30%, and 31% respectively. The thickness of the intermediate billet after rough rolling is 40mm. The finishing rolling adopts 7 passes, the cumulative compression ratio is 8.0, the finishing rolling adopts constant speed rolling, and the finishing rolling exit speed is 5.8m / s. The laminar cooling opening temperature is 839℃, the first stage water cooling cooling rate is 15.7℃ / s, the air cooling temperature is 700℃, the air cooling time is 11.0s, the second stage water cooling cooling rate is 43.2℃ / s, and the coiling temperature is 154℃.

[0069] The steel microstructure of Example 3 is 85.7% ferrite and 14.3% martensite, with an average grain size of 6.5 μm. The microstructure morphology is shown in the attached Figure 4 , yield strength 456MPa, tensile strength 639MPa, yield strength ratio 0.71, elongation 26.5%, 180° cold bending d=0 without cracking.

[0070] Comparative Example 1

[0071] The process flow of converter-LF electric heating-RH vacuum refining-continuous casting was adopted to prepare a steel billet with a thickness of 230 mm and the following chemical compositions by weight percentage: 0.07% C, 1.10% Mn, 0.13% Si, 0.010% P, 0.005% S, 0.041% Als, 0.55% Cr, 0.021% Nb, and the rest being Fe and unavoidable impurities.

[0072] The steel billet is heated-rough rolling-hot coil box-finishing rolling-laminar cooling-slow cooling process to prepare a 4.0mm thick steel plate. The specific process is as follows: the slab is cold loaded into the furnace, the heating temperature is 1211℃, and the furnace time is 160min. The rough rolling adopts 6 passes, and the deformation of each pass is 19%, 21%, 24%, 27%, 30%, and 30% respectively. The thickness of the intermediate billet after rough rolling is 40mm, and the finishing rolling exit speed is 5.7m / s. The laminar cooling opening temperature is 815℃, the first stage water cooling cooling rate is 16.1℃ / s, the air cooling temperature is 699℃, the air cooling time is 7.5s, the second stage water cooling cooling rate is 55.2℃ / s, and the coiling temperature is 70℃.

[0073] The steel microstructure of Comparative Example 1 is 68.2% ferrite and 31.8% martensite, and the martensite is distributed in a chain-like manner, with an average grain size of 8.0 μm. The microstructure morphology is shown in the attached Figure 5, yield strength 426MPa, tensile strength 709MPa, yield strength ratio 0.60, elongation 26.5%, 180° cold bending d=0 cracking. Since the cooling rate of the second stage of water cooling of the steel in comparative example 1 is too high, and the coiling temperature is too low, at the same time, when the Mn content is 1.10%, the air cooling temperature is 7.5s, which is relatively low, resulting in a high martensite content of 31.8%, resulting in a high tensile strength of more than 700MPa. At the same time, due to the chain-like segregation distribution of martensite, the plasticity of the material is reduced, resulting in cracking in the 180° cold bending test.

[0074] Comparative Example 2

[0075] A steel billet with a thickness of 200 mm and chemical composition as follows by weight percentage was prepared by a converter-LF electric heating-RH vacuum refining-continuous casting process: 0.07% C, 0.80% Mn, 0.29% Si, 0.011% P, 0.007% S, 0.032% Als, 0.57% Cr, 0.023% Nb, and the rest was Fe and unavoidable impurities.

[0076] The steel billet is heated-rough rolling-hot coil box-finishing rolling-laminar cooling-slow cooling process to prepare a 4.5mm thick steel plate. The specific process is as follows: the steel billet is sent into the slab heating furnace by hot delivery and hot loading, the furnace temperature is 1202℃, and the furnace time is 150min. Rough rolling adopts 5 passes, and the deformation of each pass is 20%, 22%, 26%, 32%, and 33% respectively. The thickness of the intermediate billet after rough rolling is 42mm, and the finishing rolling exit speed is 6.0m / s. The laminar cooling opening temperature is 841℃, the first stage water cooling cooling rate is 26.5℃ / s, the air cooling temperature is 623℃, the air cooling time is 10.0s, the second stage water cooling cooling rate is 41.7℃ / s, and the coiling temperature is 190℃.

[0077] The steel microstructure of Comparative Example 2 is 71.0% ferrite and 29.0% pearlite, with an average grain size of 8.0 μm. The microstructure morphology is shown in the attached Figure 6 , yield strength 441MPa, tensile strength 597MPa, yield strength ratio 0.74, elongation 26.5%, 180° cold bending d=0 without cracking. Since the air cooling temperature of the steel in Comparative Example 2 is relatively low and has entered the pearlite transformation range, ferrite pearlite transformation has occurred in the air cooling stage and no martensite structure has been formed.

[0078] Comparative Example 3

[0079] The steel billet with a thickness of 230 mm and the following chemical compositions by weight percentage were prepared by the converter-LF electric heating-RH vacuum refining-continuous casting process: 0.07% C, 1.00% Mn, 0.20% Si, 0.010% P, 0.007% S, 0.033% Als, 0.62% Cr, 0.013% Nb, and the rest was Fe and unavoidable impurities.

[0080] The steel billet is heated-rough rolling-hot coil box-finishing rolling-laminar cooling-slow cooling process to prepare a 5.5mm thick steel plate. The specific process is as follows: the slab temperature is 1220℃, and the furnace time is 144min. The rough rolling adopts 6 passes, and the deformation of each pass is 20%, 21%, 24%, 27%, 30%, and 31% respectively. The thickness of the intermediate billet after rough rolling is 39mm, and the finishing rolling exit speed is 6.0m / s. The laminar cooling start temperature is 840℃, the first stage water cooling cooling rate is 15.9℃ / s, the air cooling temperature is 698℃, the air cooling time is 9.0s, the second stage water cooling cooling rate is 19.0℃ / s, and the coiling temperature is 500℃.

[0081] The steel microstructure of Comparative Example 3 is 78.0% ferrite and 22.0% pearlite, with an average grain size of 10.0 μm. The microstructure morphology is shown in the attached Figure 7 , yield strength 434MPa, tensile strength 588MPa, yield strength ratio 0.74, elongation 24.5%, 180° cold bending d=0 without cracking. Since the cooling rate of the second stage of the steel in Comparative Example 3 is low and the coiling temperature is high, the ferrite-martensite dual-phase structure is not formed, and the ferrite and pearlite structures are formed at a higher phase transformation temperature.

Claims

1. A method for controlling the microstructure content in dual-phase steel, characterized in that: The dual-phase steel comprises the following chemical components by weight percentage: C: 0.05% to 0.07%, Mn: 0.55% to 1.15%, Si: 0.10% to 0.30%, P≤0.020%, S≤0.010%, Als: 0.030% to 0.050%, Cr: 0.50% to 0.70%, Nb: 0.010% to 0.030%, and the rest is Fe and unavoidable impurities; The production process of the dual-phase steel is smelting-refining-continuous casting-slab heating-rough rolling-finishing rolling-laminar cooling-coiling process; wherein, the laminar cooling adopts water cooling + air cooling + water cooling, the starting cooling temperature is 800°C to 850°C, the first stage water cooling cooling rate is 10°C / s to 30°C / s, after cooling to 680°C to 700°C, air cooling is performed, the air cooling time is 6s to 12s, the second stage water cooling cooling rate is 20°C / s to 50°C / s, and cooling is performed to 100°C to 200°C.

2. The method for controlling the microstructure content in dual-phase steel according to claim 1, characterized in that: When 0.55%≤Mn<0.75%, control the air cooling time to be 6s≤6s<8s.

3. The method for controlling the microstructure content in dual-phase steel according to claim 1, characterized in that: When 0.75%≤Mn<0.95%, control the air cooling time to 8s≤<10s.

4. The method for controlling the microstructure content in dual-phase steel according to claim 1, characterized in that: When 0.95%≤Mn≤1.15%, control the air cooling time to be 10s≤12s.

5. The method for controlling the microstructure content in dual-phase steel according to claim 1, characterized in that: In the slab heating process, the slab heating temperature is 1190°C ~ 1230°C, the slab time in the furnace is ≥100min when hot charged, and the slab time in the furnace is ≥150min when cold charged.

6. The method for controlling the microstructure content in dual-phase steel according to claim 1, characterized in that: In the rough rolling process, 5 to 6 rolling passes are adopted, and the reduction in a single pass is ≥ 18%.

7. The method for controlling the microstructure content in dual-phase steel according to any one of claims 1 to 6, characterized in that: In the finishing rolling process, at least one of the following is met: Finish rolling adopts 6 to 7 rolling passes, with a cumulative compression ratio of 6 to 12; The finishing rolling adopts constant speed rolling, and the finishing rolling exit speed is 5.5m / s~6.0m / s; The thickness of the steel plate obtained after finish rolling is 3.0 mm to 6.0 mm.

8. Dual-phase steel, characterized by: The method is prepared by any one of claims 1 to 7.

9. The dual-phase steel according to claim 8, characterized in that: The microstructure thereof is ferrite + martensite, wherein the volume fraction of ferrite is 85% to 90%, the volume fraction of martensite is 10% to 15%, and the average grain size is 5μm to 15μm.

10. The dual-phase steel according to claim 8 or 9, characterized in that: Its yield strength is 330MPa-470MPa, tensile strength is 580MPa-700MPa, elongation is ≥24%, yield strength ratio is ≤0.80, and 180° cold bending test d=0 is qualified.